The Earnings Difference of Workers in Indonesia: 2007 and 2014 - Aryo Prabowo (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2021)
The purposes of this study are to measure the earnings difference and the factors that influence earnings difference between 2007 and 2014 using data sourced from the Indonesian Family Life Survey (IFLS) in 2007 and 2014. The income determinant analysis results found that the longer a person's education year and work experience, the higher the income. Income will be even greater if someone is a man, lives in urban areas, and works in the non-agriculture sector. Moreover, there is no evidence that religion and ethnicity affect income. Then, I used the Blinder-Oaxaca decomposition method to distinguish the factors contributing to the difference in income to be explained factors and unexplained factors. It was found that that the income gap between 2007 and 2014 was 13.2 percentage points. Endowment factor contribution is more significant than unexplained factors. Furthermore, decomposition at different income levels shows that the endowment factor's effect on earning difference is getting smaller at higher income levels.